ОСНОВЫ ПУБЛИЧНОГО ВЫСТУПЛЕНИЯ (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2025)
The article is devoted to the study of the basics of public speaking as an essential element of professional and personal development. It examines the key stages of speech preparation, features of interaction with the audience, and methods of overcoming nervousness. Special attention is paid to verbal and non-verbal communication aspects, the role of confidence, and emotional expressiveness in public speaking.